Spatial arrangement and density effects on an annual cotton/cowpea/maize intercrop. I. Agronomic efaciency - Bezerra Neto, Francisco; Robichaux, Robert H. (Pesquisa Agropecuaria Brasileira, 1996)
Field experiments were conducted in Tucson, Arizona, to examine the effects of spatial arrangement and density on the agronomic efficiency of an annual cotton/cowpea/maize intercrop. The major results were: (1) the Land Equivalent Ratio (LER) for yield was higher in, the spatial arrangement of single rows of cowpea and maize between single rows of cotton, (2) cowpea proportional LER for yield was higher in the spatial arrangements in. which cowpea and maize were grown in separate rows, whereas maize proportional LER for yield was higher in the spatial arrangements in. which cowpea and maize were grown in the same rows; (3) cotton and cowpea proportional LERs for yield decreased, whereas maize proportional LER for yield increased, as cowpea/maize density in-creased from, 20,000 to 50,000 plarits ha-1; (4) LERs for biornass and yield were not affected as cotton density increased from 25,000 to 75,000 plants ha-1, and (5) partial LERs for biornass and yield were higher titan expected in. the various treatments much more frequently for maize than for cotton or cowpea.